Forensic Accounting and Investigations in the Fight Against Money Laundering (The Journal of Forensic Accounting Profession, 2025)
In the context of increasing challenges in the fight against financial crime, this paper analyzes the significance of forensic accounting in identifying suspicious transactions within the financial sector, with the aim of strengthening efforts to combat money laundering in Bosnia and Herzegovina (BiH). Money laundering is a complex form of financial crime that can be committed by individuals or large organizations. This form of financial crime is known from individuals to large organizations, and over time, different methodologies for carrying it out have developed. The detection and prevention of money laundering and the financing of terrorist activities in BiH are regulated by the Law on the Prevention of Money Laundering and Financing of Terrorist Activities (“Official Gazette of BiH,” No. 13/24), as well as the Rulebook on the Implementation of the Law on the Prevention of Money Laundering and Financing of Terrorist Activities (“Official Gazette of BiH,” No. 41/15 and 24/23). This paper aims to identify weaknesses in the financial and regulatory oversight systems in BiH. It also explores the level of understanding of forensic accounting techniques and money laundering mechanisms within organizations in the country, and assesses their impact on the overall effectiveness of anti-money laundering efforts.(Previously published on Sciendo: https://sciendo.com/article/10.2478/jfap-2025-0005, pod licencom CC BY-NC-ND 4.0)
Keywords: money laundering; money laundering prevention; money laundering indicators; financial audit; forensic accounting